2022
DOI: 10.3233/jpd-213113
|View full text |Cite
|
Sign up to set email alerts
|

Does Ethnicity Influence Recruitment into Clinical Trials of Parkinson’s Disease?

Abstract: Background: Lack of participation of black and minority ethnic communities (BAME) in registered clinical trials is a concern as data emerging from these studies are used to licence new drugs or other interventions, even though findings made in such selected study populations have limited external validity in the aforesaid ethnic groups. Objective: We used Parkinson’s disease (PD), the fastest rising neurodegenerative disorder in the world, as an exemplar condition to test our hypothesis that participants from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 44 publications
(27 reference statements)
0
16
0
Order By: Relevance
“…The data was a board re ection in line with the recent studies published from our group in trials related to Parkinson's disease (PD) as an exemplar. A detailed survey of clinical trials in PD from 2017 to 2021 showed a shocking lack of recruitment of EM subjects to clinical trials[9]. In another study from our group, a concerning signi cant lack of analgesia was reported in black PD subjects with pain compared to white Caucasian PD subjects with pain[19].…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…The data was a board re ection in line with the recent studies published from our group in trials related to Parkinson's disease (PD) as an exemplar. A detailed survey of clinical trials in PD from 2017 to 2021 showed a shocking lack of recruitment of EM subjects to clinical trials[9]. In another study from our group, a concerning signi cant lack of analgesia was reported in black PD subjects with pain compared to white Caucasian PD subjects with pain[19].…”
mentioning
confidence: 83%
“…Despite this work and a wide literature existing concerning the need for the inclusion of ethnic minorities (EM) in research [8], a recent report demonstrates that little effort has been made to promote diversity in research and in real terms, where diverse populations are available, research recruitment remains largely limited to white Caucasian, middle class, educated individuals [9]. In addition, a pre-pandemic systematic review investigating researcher reported strategies for non-white recruitment into clinical trials in the United Kingdom highlighted that limited strategies have been employed to increase recruitment among ethnic minorities [10].…”
Section: Introductionmentioning
confidence: 99%
“…Another aspect to consider while addressing inequalities of care in the context of CDD is that even the most recent long‐acting levodopa‐based treatments, such as IPX‐203 (a new extended release levodopa/carbidopa), 27 subcutaneous levodopa/carbidopa or foslevodopa/foscarbidopa, 28 as well as the Accordion Pill (delivery based on gastric retention of multilayer films containing immediate‐ and controlled‐release levodopa/carbidopa) 29 among others, have been investigated in clinical trials recruiting almost entirely White patients, with a small number of patients belonging to ethnic minorities 30 . This has been recently highlighted by a study conducted by Lau and colleagues, 30 showing that the inclusion of under‐represented ethnic minorities groups in recently published clinical trials for PD is only 21.57%, and is not even considered in most studies. This constitutes a severe underrepresentation when compared to the proportion, for example, of Black or African American in the UK and United States (US) population 30 .…”
Section: Existing Inequalities In Research and Healthcarementioning
confidence: 99%
“…The under-representation of different socioeconomic and ethnic groups, as well as women in PD research, result in an incomplete picture of the true impact on individual quality of life. [ 4 7 ]…”
Section: Introductionmentioning
confidence: 99%